PENGEMBANGAN MODEL BISNIS PADA PT. SAHIBUNA SABILA SALAM BUKITTINGGI MENGGUNAKAN BUSINESS MODEL CANVAS (BMC) - Ilham Yoga Pratama; Rusydi Fauzan (Jurnal Ekonomi dan Bisnis, 2025)
The issue addressed in this study is the absence of a comprehensively structured business model and the stagnation in business growth due to suboptimal development strategies. The objective of this research is to identify the currently implemented business model and to design an innovative and adaptive future business model that responds to market changes. This study employs a descriptive qualitative method with data collection techniques including in-depth interviews, observation, documentation, and literature review. The collected data were analyzed by identifying the nine elements of the Business Model Canvas (BMC), evaluated through SWOT analysis to understand the strengths, weaknesses, opportunities, and threats, and further analyzed using the Blue Ocean Strategy (BOS) framework to design a development strategy based on value innovation. The research findings indicate that PT. Sahibuna Sabila Salam needs to strengthen several elements such as customer segmentation, value proposition, distribution channels, and customer relationships. Through the designed Future BMC, the company is directed to create new value, enhance digital services, and reach untapped markets. The conclusion of this study is that the application of BMC, combined with SWOT and BOS, provides a more effective strategic direction for business development. The implication of this research encourages the company to immediately implement the newly designed business model in order to enhance competitiveness and ensure sustainability in the umrah travel industry